Disparity in the natural cycles of Borrelia burgdorferi and the agent of human granulocytic ehrlichiosis. - Levin, M L (Centers for Disease Control and Prevention, 1999)
We studied the prevalence of Borrelia burgdorferi and the agent of human granulocytic ehrlichiosis (HGE) among questing nymphal and adult Ixodes scapularis ticks of the same generation and the infectivity of wild white-footed mice for ticks feeding on them. The prevalence of B. burgdorferi infection in host-seeking ticks increased less than twofold from nymphal (31% to 33%) to adult (52% to 56%) stage, and 52% of white-footed mice were infected. Prevalence of the agent of HGE increased 4.5- to 10.6-fold from nymphal (1.5% to 1.8%) to adult stage (7.6% to 19.0%), while only 18% of mice were infectious to ticks. B. burgdorferi infection was more common in mouse-fed ticks than in ticks collected from vegetation, whereas the agent of HGE was half as common in mouse-fed ticks as in ticks collected from vegetation. The different prevalence in nature of these pathogens in ticks suggests that their maintenance cycles are also different.